Prophylactic replacement of Björk-Shiley convexo-concave heart valves: an easy-to-use tool to aid decision-making in individual patients. - Steyerberg, E. W. (1996)
OBJECTIVE: To develop an easy-to-use tool for decision-making on prophylactic replacement of Björk-Shiley convexo-concave heart valves. DESIGN: Decision analysis comparing elective replacement with observation. SETTING: Referral centres for patients with artificial heart valves. PATIENTS: Quantitative estimates were obtained from a follow up study conducted in The Netherlands, including 2303 patients with a mean follow up of 6.6 years and from recently published studies. INTERVENTION: Elective valve replacement with a new artificial heart valve. MAIN OUTCOME MEASURE: Loss of life-expectancy. RESULTS: A simple graph was constructed to present the loss of life-expectancy caused by strut fracture for combinations of basal life-expectancy (life-expectancy without strut fracture) and lethal fracture risk (strut fracture risk multiplied by lethality of fracture). This loss can be compared directly with the loss of life-expectancy caused by surgical mortality. This quantitative approach takes into account individual patient characteristics, such as age, gender, cardiac comorbidity, and position of the valve, but the final estimation of surgical mortality also requires clinical judgement. The calculations can be made easily by hand or with a simple computer application. CONCLUSIONS: This decision support tool enables the direct estimation of the gain or loss of life-expectancy that is likely with replacement of a Björk-Shiley convexo-concave heart valve. It can be used to evaluate individual patients as well as groups of patients, and allows for easy incorporation of revisions of fracture risk estimates.